MECHANICAL DAMAGE ASSESSMENT IN CONCRETE BEAMS REINFORCED WITH STEEL AND POLYPROPYLENE FIBERS USING ULTRASONIC PULSE VELOCITY TESTING - Sanchez Alvarado, Andrés G.; Ospina García, Miguel Ángel; Carrillo León, Wilmer Julian; Parra Gomez, Yohana Catalina; Chaves Pabón, Saieth Baudilio (Journal of Applied Engineering Science, 2026)
Concrete beams are structural elements primarily subjected to vertical loads, including self-weight (dead load) and externally applied actions (live load). The sustained interaction of these loads induces bending deformations. As with all structural materials, concrete beams experience mechanical damage when the applied stresses exceed their ultimate capacity, typically manifested through cracking, which occurs on the tensile face opposite the load application. For several decades, fiber reinforcement has been employed worldwide to enhance the physical and mechanical properties of concrete, particularly its residual strength and crack control. In this study, concrete specimens were reinforced with two types of fibers—steel and polypropylene—and evaluated using ultrasonic pulse velocity (UPV) testing to characterize mechanical damage. After curing time, UPV measurements were taken to assess internal damage development under flexural loading. Based on the experimental data, predictive equations are proposed to estimate mechanical damage as a function of pulse velocity, allowing for improved evaluation of reinforced concrete behavior under stress.
Keywords: Reinforced concrete; steel fibers; polypropylene fibers; non-destructive tests; mechanical damage